Economic zones and local income inequality: Evidence from Indonesia - Cecília Hornok; Dewa Gede Sidan Raeskyesa (Kiel Institute for the World Economy (IfW Kiel), 2022)
Economic zones can be powerful drivers of economic growth in developing countries. However, less is known about their distributional impact on the local society. This paper provides empirical evidence from Indonesian provinces on the relationship between economic zones and within-province income inequality. Estimates from panel regressions and synthetic control case studies suggest that this relationship is positive overall. The estimated rise in income inequality after a zone opens is relatively small on average and may be short-lived. However, the average estimate masks large regional differences, which suggests that the inequality implications of economic zone policies depend on local conditions. One explanation for the rise in inequality is that the unskilled population benefits disproportionately less from the policy. As a remedy, we propose education and training programs that target the poor and unskilled and in which companies also actively participate.
Keywords: D31; F63; O15; O25; 330; economic zones; place-based policy; income distribution; synthetic control method; Indonesia